Deep eutectic solvent for curing of phthalonitrile resin: Lower the curing temperature but improve the properties of thermosetting. (June 2021) - Qi, Yu; Weng, Zhihuan; Song, Ce; Hu, Yue; Liu, Xin; Wang, Jinyan; Zhang, Shouhai; Liu, Cheng; Jian, Xigao
Long curing duration and high curing temperature are commonly known to restrict the application of the phthalonitrile resin. In this study, a deep eutectic solvent (DES) containing ZnCl2 and urea has been developed to improve the curing process of the resorcinol-based phthalonitrile resin (DPPh) without sacrificing the useful properties of the resin. For the molar ratio of ZnCl2 and urea as 1:1 (ZnCl2 -urea (1–1)), the initial curing temperature and apparent activation energy of the system were recorded as 179.5°C and 90.1 kJ/mol, respectively, indicating a reduction of 31.2% and 39.0% as compared to the pristine ZnCl2 system. More importantly, with curing time of 6 h and post-curing temperature of 300°C, the temperature at 5% weight loss as well as glass transition temperature of the resin with DES as the curing agent were 523.1°C and 370.2°C, respectively, demonstrating a significant improvement as compared to the resin cured with ZnCl2 . In addition, the satisfactory long-term oxidation stability of the resin could also be obtained by employing the new curing agent. The findings from this study open a functional pathway for facile preparation of the high-performance curing agent for the phthalonitrile resin.